Enhancing Healthcare in Afghanistan from 2015 Through 2020: The Impact of Human Resource Management - Ali Reza Rahmani (The American Journal of Management and Economics Innovations, 2026)
This study explores the influence of Human Resource Management (HRM) on advancing healthcare in Afghanistan from 2015 to 2020 relying on data collected by international organizations and the government of Afghanistan. During this period HRM became a pivotal strategy for addressing critical workforce shortages, infrastructural gaps, and limited access to essential healthcare services. Using HRM approaches, the Ministry of Public Health leveraged collaborations with international organizations to secure vital financial and technical resources, which facilitated infrastructure development, workforce training, and healthcare service improvements. Despite challenges such as administrative corruption and political influence, HRM initiatives contributed to workforce stabilization and improved healthcare accessibility. An analysis of the data revealed Afghanistan fell much below global health standards regarding healthcare manpower as well as medical facilities and resources. Specialist doctors and healthcare professionals were particularly scarce, especially in rural regions and provinces. The objective of the study is to assess the effectiveness of HRM strategies in improving healthcare delivery, particularly in underserved areas. This study further examines the role of international collaborations and offers recommendations for sustaining and advancing healthcare improvements in Afghanistan. Results indicate that while HRM interventions led to progress in infrastructure, access, and human resource development, significant disparities remain in gender representation, specialty distribution, and rural healthcare coverage.